Pemanfaatan Bahan Ajar Berupa Komik dalam Pembelajaran IPS - Angelina, Dwi Yanti; Suhardjo, Suhardjo; Hardi, Ode Sofyan (Universitas Negeri Makassar, 2021)
This study aims to determine the benefits of teaching materials in the form of comics as social studies learning in geography content. The method used is descriptive method. The population in this study were students of SMPN 62 Jakarta and the research sample was students of class VII.5 totaling 37 students. The analysis technique in this study used an online questionnaire with a Likert scale and a gain test that was conducted to determine the level or magnitude of the influence of the use / utilization of comic media. The sampling technique is simple random sampling. The results of the study were based on validation by comics experts and material experts which were declared fit for use as teaching materials in the social studies learning process with geographic content. The influence of the use of comics in social studies learning with geographic content can be seen from calculations through the gain test and the Likert scale. The results of the pretest and posttest which show the high category, namely 0.8 in the calculation of the gain test. Furthermore, through the calculation of the Likert scale, the percentage of respondents' answers shows that 80% is in the feasible category.